An overview on Azelaic Acid: Biosynthesis, signalling and the action under stress conditions in plants - Dinler, Burcu Seckin; Cetinkaya, Hatice (Journal of Plant Stress Physiology, 2024)
Plants are exposed to various biotic and abiotic stress factors throughout their lives. For this reason, they have developed some defense mechanisms. They can induce systemic acquired resistance (SAR), which provides long-lasting protection against diverse pathogen attacks. In recent years, several chemical inducers (salicylic acid, glyceraldehyde-3-phosphate, azelaic acid, pipecolic acid, and dehydroabietic acid) have been determined to play roles in this mechanism. The transfer of these signal molecules from infected tissue to non-infected tissues through phloem provides potent defence communication. Azelaic acid is a well-known molecule that triggers salicylic acid accumulation under biotic stress as a priming factor to induce SAR, although little is known about its role under abiotic stress. Here, this review aims to call attention to the effects of AzA under abiotic stress conditions as well as biosynthesis, transport and signalling.